2016
DOI: 10.1016/j.precisioneng.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Parallel-kinematics XYZ MEMS part 1: Kinematics and design for fabrication

Abstract: Micro-and nanopositioning systems are widely used in the field of nanotechnology for probing, imaging, and increasingly for processing. This two-part set of papers presents a MEMS-scale parallel-kinematics mechanism, designed to achieve pure spatial (X, Y and Z) translation. With three independent kinematic chains connecting the end-effector to the base, a fully functional mechanism with axis actuation and displacement sensing is realized in a double device layer ("oreo") SOI wafer using only conventional, mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…The designed device is expected to be a general-purpose, MEMS-scale, spatial positioning platform that can be adapted to several possible applications. Motivated by applications in nano-indentation, confocal microscopy, scanned probe microscopy, the design objectives are to realize an in-substrate, low-profile stage based on the kinematic scheme developed in [1], and actuated by electrostatic drives. The stage is designed to have workspace capable of embedding a cube of dimension 20μm x 20μm x 20μm and is to be actuated by electrostatic drives with a maximum voltage of less than 150V.…”
Section: Device Architecturementioning
confidence: 99%
See 3 more Smart Citations
“…The designed device is expected to be a general-purpose, MEMS-scale, spatial positioning platform that can be adapted to several possible applications. Motivated by applications in nano-indentation, confocal microscopy, scanned probe microscopy, the design objectives are to realize an in-substrate, low-profile stage based on the kinematic scheme developed in [1], and actuated by electrostatic drives. The stage is designed to have workspace capable of embedding a cube of dimension 20μm x 20μm x 20μm and is to be actuated by electrostatic drives with a maximum voltage of less than 150V.…”
Section: Device Architecturementioning
confidence: 99%
“…n the companion paper [1], we have discussed the kinematics, dynamics and design approach to a parallel-kinematics, MEMSscale, spatial translation stage concept (referred to as a PK-XYZ-MEMS stage), realizable on a double device layer silicon-oninsulator (SOI) substrate. We have shown that the forward position kinematics problem is reduced to a sixth-order polynomial equation, and that the inverse position kinematics problem admits closed-form solution.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most complete electrostatic actuators has been demonstrated by Correa et al [22] and Koo et al [20] in their partner articles. Their device is capable of moving in a 20 µm cube using a silicon-on-insulator (SOI) process and closed loop control.…”
Section: Introductionmentioning
confidence: 99%